PERAN PUSTAKAWAN DALAM MENINGKATKAN JIWA KEWIRAUSAHAAN PADA PESERTA DIDIK (Studi Kasus Di SMK N 1 Mesjid Raya) - Rahmawati Rahmawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Writing this paper aims to describe the role of librarians in improving the entrepreneurial spirit of students. The role of librarians in improving the entrepreneurial spirit of students is carried out in several stages (1) Librarians ask for syllabus to productive subject teachers (2) Librarians collect materials to be used as teaching materials (3) Librarians provide teaching materials for productive teachers (4) Librarians become solution makers to solve problems in finding information (5) Librarians create vocational reading corners to promote student work. The instrument was used to obtain data from the documentation of the list of student products before there was a vocational reading corner, namely in 2018 and after the reading corner was in 2019. The results of this study are that librarians have a role in increasing the entrepreneurial spirit of students.